Health Education in Adolescents about Stress Management in Dealing with the COVID-19 Vaccine Program: Pendidikan Kesehatan pada Remaja tentang Manajemen Stres dalam Menghadapi Program Wajib Vaksin COVID-19 - Afandi, Alfid Tri; Asmaningrum, Nurfika; Ardiana, Anisah (Journal of Community Empowerment for Multidisciplinary (JCEMTY), 2023)
COVID-19 is an outbreak that began to spread in early 2020. The impact caused by this virus is hazardous in causing death for those infected. Indonesia itself is a country with a high risk of death due to the Covid-19 virus. East Java has the 3rd highest number of cases at the provincial level, and Jember Regency has the 4th highest. To increase youth's knowledge regarding the mechanism of COVID-19 transmission and stress management in the face of the COVID-19 pandemic and the mandatory COVID-19 vaccine program. The goal is that teenagers are not afraid to receive the Covid-19 vaccine. Empowerment of youth and health cadres in conducting counseling using leaflets, PowerPoint presentations, and interactive discussions. The implementation of this activity resulted in the formation of teenagers ready for the COVID-19 vaccine and increased knowledge and awareness of how to prevent the transmission of the COVID-19 virus. After carrying out this community service activity, it is hoped that teenagers, health cadres, and village officials will always actively support government programs to prevent the spread of the Covid-19 virus.